Analysis of the Rollover Stability of Four-Wheeled Vehicles on Curved and Banked Roads - Yalemzewd Ytayew Shiferaw; Bisrat Yoseph Gebereyesus; Velmurugan Paramasivam (The Scientific World Journal)
A trustworthy index that accurately displays real-time rollover danger during vehicle maneuvers in order to design a rollover prevention system is critical to have. In this present work, the rollover of four-wheeled vehicles on banked curves is investigated. The mathematical model is the vehicle’s rollover index on a banked curve, which is based on the lateral load transfer ratio (LTR) principle. The LTR takes the track width, location of the center of gravity, and vehicle mass as major vehicle parameters and also longitudinal velocity, lateral acceleration, road radius, steering angle, and bank angle as major state variables. The sensitivity analysis showed rollover is more sensitive to track width with a sensitivity coefficient of 1 and then to forward velocity with a sensitivity coefficient of 0.89. Distance between CGs, lateral acceleration, turning radius, and distance of CG from roll center have also a sensitivity coefficient of 0.81, 0.7, 0.69, and 0.63, respectively.